A study on the attitudes of 12th grade students in listenning lessons at a high school in Bac Ninh province = Nghiên cứu thái độ của học sinh lớp 12 trong giờ học nghe tại một trường THPT tại tỉnh Bắc Ninh. M.A Thesis Linguistics : 60 14 01 - Đỗ, Thu Hà, 1985- (University of Languages and International Studies, 2017)
M.A. Thesis English Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013